2022
DOI: 10.54548/njps.v37i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hypertensive Effects of Anthocyanins from Hibiscus sabdarifa Calyx on the Renin-Angiotensin-Aldoslestrone System in Wistar Rats

Abstract: Hibiscus sabdariffa (HS) has gained attention as an anti-hypertensive agent. In the present study, we hypothesized that anthocyanins from HS may attenuate salt-induced hypertension in rats by suppressing the components of renin-angiotensin-aldoslestrone system (RAAS). Hypertension was induced in the rats by adding 8% NaCl in their diet for six weeks. Wistar rats (n=5 each) were randomly divided into seven groups. Group 1 was the normentensive control group and was fed with normal rat chew and water ad libitum;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As shown by Xu et al, intracranial infusion of anthocyanin extract decreased the sympathetic nervous system activity and reduced blood pressure in salt-induced hypertensive rats [329]. Furthermore, anthocyanins administered at 50, 100, or 200 mg/kg decreased systolic and diastolic blood pressure as well as heart rate in hypertensive rats in a dose-dependent manner, at least in part through RAAS inhibition [330].…”
Section: • Vascular Function Hypertensionmentioning
confidence: 80%
“…As shown by Xu et al, intracranial infusion of anthocyanin extract decreased the sympathetic nervous system activity and reduced blood pressure in salt-induced hypertensive rats [329]. Furthermore, anthocyanins administered at 50, 100, or 200 mg/kg decreased systolic and diastolic blood pressure as well as heart rate in hypertensive rats in a dose-dependent manner, at least in part through RAAS inhibition [330].…”
Section: • Vascular Function Hypertensionmentioning
confidence: 80%
“…Xu et al [ 179 ] showed that chronic infusion of anthocyanins into the paraventricular nucleus of rats with salt-induced hypertension reduced BP and peripheral sympathetic nerve activity. Anthocyanins from Hibiscus sabdariffa reduced salt-induced hypertension in rats by inhibiting components of the renin–angiotensin–aldosterone system [ 178 ]. Yamane et al [ 165 ] reported that supplementing a standard diet with 10% freeze-dried chokeberries reduced BP in spontaneously hypertensive rats.…”
Section: The Effects Of Anthocyanins On the Prevention And Supportive...mentioning
confidence: 99%
“…Previous studies reported that these phytochemical compounds showed inhibitory activities against ACE and could lower blood pressure. 7,27,[41][42][43][44] 33,45 The complexes caused the enzyme to lose its affinity to bind with the substrate, resulting in no conversion of angiotensin-I to angiotensin-II. 2 In addition, phenolic acids and anthocyanins in H. sabdariffa have a vasorelaxant effect, which helps lower blood pressure.…”
Section: Ace Inhibitory Activities Of the Hs Cs And Hc Infusionsmentioning
confidence: 99%